Cytologic Differential Diagnosis of Malignant Mesothelioma and Reactive Mesothelial Cells With FISH Analysis of p16. Issue 7 (15th April 2016) - Hiroshima, Kenzo; Wu, Di; Hasegawa, Mizue; Koh, Eitetsu; Sekine, Yasuo; Ozaki, Daisuke; Yusa, Toshikazu; Walts, Ann E.; Marchevsky, Alberto M.; Nabeshima, Kazuki; Tada, Yuji; Shimada, Hideaki; et al.
Abstract : Background: Mesothelioma patients often present with serosal effusions, which are ideal for cytopathological diagnoses. However, the morphological overlap between malignant and benign mesothelial proliferation can make a conclusive cytological diagnosis of mesothelioma elusive because immunohistochemical staining does not discriminate definitively between the two in this setting. p16 is deleted in up to 80% of pleural mesotheliomas. The aim of this study was to establish the correlation between the p16 deletion status of the cell block with that of its corresponding tumor using fluorescence in situ hybridization (FISH) analysis for individual patient tumors. Methods: Twenty‐two biopsies and 24 corresponding cell blocks, containing serosal effusions with atypical mesothelial cells from 22 patients with histologically confirmed pleural mesotheliomas, were analyzed with p16 FISH. Seventeen cell blocks consisting of serosal effusions with reactive mesothelial cells from nonmesothelioma cases were also analyzed. Combined immunofluorescence and FISH were also performed. Results: Seventeen of the 22 mesothelioma patients (77.3%) showed homozygous deletions of p16 in the tumor tissue and in the atypical mesothelial cells from the cell blocks. p16 FISH followed by immunofluorescence with EMA was helpful towards identifying the mesothelioma cells in the cell blocks. Conclusion: We confirmed that the p16 FISH results obtained from the cell blocks are as reliable as those from the tissue sections. Cell block analysis is recommended for patients with serosal effusions of unknown origins with the following methods: immunohistochemistry should be performed to validate the mesothelial origin, and p16 FISH should be performed to confirm malignancy. Diagn. Cytopathol. 2016;44:591–598. © 2016 Wiley Periodicals, Inc.